Growing tips of type I collagen fibrils formed in vitro are near-paraboloidal in shape, implying a reciprocal relationship between accretion and diameter. - Holmes, D F (1992)
Collagen fibrils generated in vitro at 37 degrees C by enzymic removal of C-terminal propeptides from type I pC-collagen (an intermediate in the normal processing of type I procollagen to collagen containing the C-terminal propeptides but not the N-terminal propeptides) display shape polarity, with one tip fine tapered and the other coarse tapered. Mass measurements by scanning transmission electron microscopy show that the mass per unit length along both kinds of tip increases roughly linearly over distances of approximately 100 D periods from the fibril end [D (axial periodicity) = 67 nm]. The fine tips of fibrils of widely differing lengths exhibit near-identical mass distributions, the mass in all cases increasing at the rate of approximately 17 molecules per D period, irrespective of fibril length. Coarse tips display less regular behavior. These results show that (i) the shape of a fine tip is not conical but resembles more closely a paraboloid of revolution, and (ii) for this shape to be maintained throughout growth, accretion (rate of mass uptake per unit area) cannot everywhere be the same on the surface of the tip but must decrease as the diameter increases. To a first approximation, accretion alpha (diameter)-1.